GENOTIPE HPV DAN POLA INFEKSINYA TERKAIT JENIS HISTOPATOLOGI KANKER LEHER RAHIM (HPV Genotype and HPV Infection Pattern Related to the Histopathological Type of Cervical Cancer) - Roudhotul Ismaillya Noor; Aryati Aryati; Pudjo Hartono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Uterine cervical cancer is the number one cause of female cancer in Indonesia. The most common cause is a persistent infection with ahigh risk of HPV (Human Papilloma Virus). A multiple genotype HPV infection with high risk HPV increases the poor prognosis of cervicalcancer. Non-squamous type of cervical cancer has a poorer prognosis than the squamous type. The aim of this study was to know theassociation between HPV genotype and HPV infection pattern with histopathological type of cervical cancer in patients of the Dr. SoetomoHospital, Surabaya. This study was an analytical observational-cross sectional research. The samples consisted of 44 uterine cervicalswabs from the Oncology Out-Patient Clinic, proven and diagnosed as the related cervical cancer in October-November 2012. PCR resultsshowed 33 HPV positive, seven (7) HPV negative and 4 invalid. The Fisher’s exact test was only done for the 33 positive HPV samples.The positive HPV samples consisted of 24 squamouse and nine (9) non-squamous types of uterine cervical cancer. A 90.9% (30/33) highrisk HPV genotypes was found in 72.7% (24/30) squamous and 18.2% (6/30) non-squamous types. Multiple genotype HPV infection9.1% (3/33) occurred in 3% (1/3) squamous and 6.1% (2/3) non-squamous types. There was a significant association between HPVgenotype and histopathological type of the uterine cervical cancer (p=0.015). There was no association between HPV infection patternand histopathological type of uterine cervical cancer (p=0.174). Negative HPV and low risk HPV genotypes can be found in uterine cervicalcancer patients of the Dr. Soetomo Hospital, Surabaya. Multiple genotype HPV infections have a 2.86 times greater risk in developingnonsquamous type with a poor prognosis.